2007
DOI: 10.1128/jb.01410-06
|View full text |Cite
|
Sign up to set email alerts
|

SRP19 Is a Dispensable Component of the Signal Recognition Particle in Archaea

Abstract: In vitro, archaeal SRP54 binds SRP RNA in the absence of SRP19, suggesting the latter to be expendable in Archaea. Accordingly, the Haloferax volcanii SRP19 gene was deleted. Although normally transcribed at a level comparable to that of the essential SRP54 gene, SRP19 deletion had no effect on cell growth, membrane protein insertion, protein secretion, or ribosome levels. The absence of SRP19 did, however, increase membrane bacterioruberin levels.Despite their structural similarities (9, 28), eukaryal and arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…Real‐time RT‐PCR was performed essentially as described (Yurist et al ., 2007) using SYBR Green PCR 2× Master Mix (Applied Biosystems, Foster City, CA). Primers (listed in Table 2) were designed using Primer Express 2.0 software (PerkinElmer Life Sciences) and employed at a final concentration of 400 nM.…”
Section: Methodsmentioning
confidence: 99%
“…Real‐time RT‐PCR was performed essentially as described (Yurist et al ., 2007) using SYBR Green PCR 2× Master Mix (Applied Biosystems, Foster City, CA). Primers (listed in Table 2) were designed using Primer Express 2.0 software (PerkinElmer Life Sciences) and employed at a final concentration of 400 nM.…”
Section: Methodsmentioning
confidence: 99%
“…These proteins have a de facto need for SRP54 for their synthesis. Although homozygous mutathe exception of the SRP RNA, SRP54 is the only one of the six SRP polypeptides that is universally conserved throughout evolution (31,32), with 96% sequence identity between human and zebrafish molecules. This high level of conservation is explained by the central role played by SRP54 in the cotranslational process that affects over one-third of the human proteome (see below).…”
Section: Discussionmentioning
confidence: 99%
“…In Eukarya, SRP19 is involved in SRP assembly and facilitates the binding of SRP54 to the SRP RNA by interacting with SRP RNA helix 8 [67][68][69][70]. Nevertheless, it has been shown that, unlike in Eukarya, archaeal SRP19 is not strictly required for the binding of archaeal SRP RNA to SRP54/Ffh [67,71,72]. The SRP19-independent binding of archaeal SRP RNA and SRP54/Ffh seems to reflect the stability of the SRP complex, which may be required for growth at extreme temperatures or pH values or in highly saline environments [68].…”
Section: The Srp Pathway In Archaeamentioning
confidence: 99%